2016
DOI: 10.1002/ejoc.201601217
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient One‐Pot Protocol for the Synthesis of Polysubstituted 4‐Amino‐iminocoumarins and 4‐Aminoquinolines by a Copper‐Catalyzed Three‐Component Reaction

Abstract: A simple and efficient synthetic approach is reported for the synthesis of highly functionalized 4‐amino‐iminocoumarins 4 and 4‐aminoquinolines 6 in moderate to excellent yields, through a copper‐catalyzed multicomponent reaction. The reaction is carried out in a one‐pot manner, using readily available terminal alkynes 1, sulfonyl azides 2, and 2‐hydroxybenzonitriles 3 or 2‐aminobenzonitrile (5) as substrates at a slightly elevated temperature under N2. The protocol is operationally simple and has a good subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Delightedly, an investigation found that N ‐(2‐pyridyl)amidines could be afforded by the efficient reaction between 2‐aminopyridines, terminal alkynes, and sulfonyl azides by using a copper salt and base. The reaction operated through ketenimine intermediates, and the transformation has been extensively reported by Chang, Wang, Lee, Wu, Yi and their respective co‐workers under extremely mild conditions. However, to our surprise, according to Chang's procedure, in addition to a complex unidentified product, the desired 2‐amino analogs ( A ) from N ‐(2‐pyridyl)amidines were not observed under the same conditions.…”
Section: Resultsmentioning
confidence: 91%
“…Delightedly, an investigation found that N ‐(2‐pyridyl)amidines could be afforded by the efficient reaction between 2‐aminopyridines, terminal alkynes, and sulfonyl azides by using a copper salt and base. The reaction operated through ketenimine intermediates, and the transformation has been extensively reported by Chang, Wang, Lee, Wu, Yi and their respective co‐workers under extremely mild conditions. However, to our surprise, according to Chang's procedure, in addition to a complex unidentified product, the desired 2‐amino analogs ( A ) from N ‐(2‐pyridyl)amidines were not observed under the same conditions.…”
Section: Resultsmentioning
confidence: 91%
“…A highly functionalized 4‐amino‐iminocoumarins (Scheme ) and 4‐aminodihydroquinolines (Scheme ) via a copper‐catalysed tandem three‐component reaction involving terminal alkynes, sulfonyl azides and 2‐hydroxybenzonitriles or 2‐aminobenzonitrile as substrates has been carried out at slightly elevated temperature under N 2 . This synthesis involves nucleophilic addition to ketenimine followed by isomerisation of the intermediate . The initial model reaction for the synthesis of 4‐amino‐iminocoumarins and 4‐aminodihydroquinolines was achieved by a reaction of o ‐hydroxybenzonitrile and o ‐aminobenzonitrile respectively with phenylacetylene and p ‐toluenesulfonyl azide in presence of CuCl (10 mol%) and TEA (1.5 mmol) in CH 2 Cl 2 (2 ml) at 80 °C for 4 h.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…4-Substituted coumarins arise from palladium(0)-promoted coupling reactions of o-methoxyboronic acids with a glutamic acid-derived (Z)v i n y l triflate followed by total deprotection with boron tribromide (Scheme 53; 17OL2797). Highly functionalized coumarins arise from an NHC-mediated three-component reaction of 2-hydroxybenzonitriles with aliphatic/aromatic terminal alkynes and tosyl/phenyl azide delivers a wide range of polysubstituted 4-aminoiminocoumarins (17EJO102).…”
Section: Coumarinsmentioning
confidence: 99%